Reliability and validity of the Healthy Home Survey: A tool to measure factors within homes hypothesized to relate to overweight in children - Tabak Rachel G; Vaughn Amber; Hales Derek; Ward Dianne S; Bryant Maria J; Stevens June (International Journal of Behavioral Nutrition and Physical Activity, 2008)
Abstract Background The contribution of the environment to the obesity epidemic is well recognized. Parents have control over their home environment and can, therefore, support healthy dietary and activity habits in their children by manipulating factors such as access to energy-dense foods, availability of physical activity equipment, and restricting screen time. This paper describes the development of the Healthy Home Survey and its reliability and validity. The Healthy Home Survey was designed to assess characteristics of the home environment that are hypothesized to influence healthy weight behaviors in children including diet and physical activity. Methods We recruited 85 families with at least one child between 3–8 years. The Healthy Home Survey was administered to parents via telephone and repeated in a random sample of 45 families after 7 days. In-home observations were performed within 14 days of the first Healthy Home Survey interview. Percent agreement, Kappa statistics, Intra-class correlation coefficients and sensitivity analyses were used to evaluate reliability and validity evidence. Results Reliability and validity estimates for the Healthy Home Survey were varied, but generally high (0.22–1.00 and 0.07–0.96 respectively), with lower scores noted for perishable foods and policy items. Lower scores were likely related to actual change in the perishable foods present and the subjective nature or clarity of policy questions and response categories. Conclusion Initial testing demonstrated that the Healthy Home Survey is a feasible, reliable, and valid assessment of the home environment; however, it has also highlighted areas that need improvement. The Healthy Home Survey will be useful in future research exploring the relationship between the home environment and child weight.